Bergers, végétariens et clochards. Sous-cultures et conduites marginales alimentaires dans le sud-ouest de la France (XVIIe-XXIe siècles) - Duhart, Frédéric (Studium, 2018)
After general comments on food cultures and their study, I consider some food subcultures and marginal ways of eating in Southwest France from the 17thcentury to the present day. I first discuss the transhumant pastoralist food cultures in Pyrenees and Aubrac. Their main characteristic was that the temporary life away from the villages led small man communities to cook daily in the absence of women that normally did in this region. Then, I consider the history of the vegetarianism/veganism in Southwest France. Jean-Antoine Gleïzès adopted his vegetarian lifestyle and wrote his books in this region. Marginal way of eating at its beginning, vegetarianism locally evolved into a real counter-culture. Lastly, I discuss the poor people marginal ways of eating, especially the homeless ones. They are adaptations to special contexts in which «being resourceful»is essential. Key words:food, cooking, shepherd, vegetarianism, homeless, marginality